Meta Analysis of Clustering Nursing for Stroke Associated Pneumonia - Chunyan HAN; Cun ZHAO; Xinglei WANG; Yali CHANG; Li YAO; Yihong KE; Jinhui TIAN; Xinman DOU (康复学报)
Objective:To evaluate the impact of clustering nursing on stroke-related pneumonia by Meta-analysis, and provide a scientific basis for improving the prognosis of stroke patients.Methods:We searched in Wanfang database, CNKI, China Biomedical Literature database, PubMed, Web of Science, EMbase, and Cochrane Library database. The objects were patients with stroke. The trials (RCTs) included randomized controlled was about clustering nursing intervention for stroke-related pneumonia. The search period is from the construction of the database to January,2018. The main outcome indicators were the incidence of stroke-related pneumonia, the incidence of aspiration, and the hospitalization, the secondary outcome indicators were hospitalization costs, mortality, and swallowing function. Two researchers independently screened the literature, extracted the data, and evaluated the quality of the included studies. The quality evaluation used the Cochrane Collaboration's bias risk assessment tool. The data was analyzed using RevMan 5.3 statistical software. The continuous variables used standardized mean difference (SMD) and 95%CI as the effect indicators. The dichotomous variables used odds ratio (OR) and 95%CI as the effect indicators. If the homogeneity between the studies was good (P≥0.1, I2≤50%), select the fixed effect model, if there was heterogeneity between these studies (P<0.1, I2>50%), analyze the source of heterogeneity, and if there was no clinical heterogeneity, choose a random effects model.Results:A total of 11 clinical randomized controlled trial literatures were finally included. They were all in Chinese, with a total of 1 048 patients. Meta analysis results showed that the incidence of SAP in the cluster care group was[OR=0.31, 95%CI (0.22,0.44), P<0.000 01], and the incidence of aspiration was[OR=0.19, 95%CI (0.10,0.33), P<0.000 01], hospitalization[lighter group: SMD=-0.82, 95%CI (-1.09,-0.54), P<0.000 01, severe group: SMD=-5.38, 95%CI (-6.02,-4.74), P<0.000 01]were significantly lower than those of the conventional nursing group, and the differences were statistically significant (P<0.05).Conclusion:Clustering nursing can prevent the occurrence of SAP, reduce the incidence of aspiration, shorten the hospitalization, and is worthy of clinical application. However, the literature data, the quality of the literature will have a greater impact on the research results. Therefore, in the next step, it is necessary to conduct more high-quality, large-sample research in strict accordance with the requirements of the experiment to provide reliable evidence for the implementation of clustering nursing evidence.